"A Line in the Tar Sands: Struggles for Environmental Justice" by Toban Black, Stephen D’Arcy, Tony Weiss, and Joshua Kahn Russell, eds. - McLean, Jacob (UnderCurrents: Journal of Critical Environmental Studies, 2017)
Review of A Line in the Tar Sands: Struggles for Environmental Justice by Toban Black, Stephen D’Arcy, Tony Weiss, and Joshua Kahn Russell, eds. (2014, Between the Lines). Find full text in .pdf below.